THE IMPORTANCE OF RESERVE OFFICER CADRES FOR THE NATIONAL SECURITY SYSTEM OF THE REPUBLIC OF SERBIA - Conić, Jovan; Đorđević, Aleksandar (The Policy of National Security, 2025)
One of the most important factors in achieving a country’s national and defense interests is its organized armed forces, which are ready at any moment to protect its independence and sovereignty. According to the National Security Strategy of the Republic of Serbia, the Serbian Armed Forces represent the most important and influential formation on which the national security system is based, to ensure security for all its citizens. Today’s armed conflicts demonstrate that, despite the need for a professional army, which is the primary carrier of combat operations, the key role on the battlefield is still played by the number of military personnel, with their inherent training and motivation. The Republic of Serbia, as a militarily neutral country with the concept of total defense, and with a vital interest in preserving its territorial integrity, is obliged to develop and improve its own army due to the risks in the security environment, in order to preserve the state and national existence. In addition to active members, the Serbian Armed Forces also consist of its reserve forces, which together represent a well-organized whole without which the concept of total defense could not function. History teaches us that the officer cadre is the spearhead of every army, and that its training and motivation are key to success. Additionally, the reserve officer cadre is also of great importance, especially in the event of war, when both are equally important. The subject of this paper is the importance of the reserve officer cadre in the defense system and its social role in peace, promoting the highest military values. The concept of training reserve officer cadres in Serbia has a long and rich history that remains alive today, but it needs to be updated in accordance with the current security challenges.